Allegorie as argument. Galasiërs 4:21-5:1 in retoriese perspektief - D. F. Tolmie (Acta Theologica)
The purpose of this article is to discuss Galatians 4:21-5:1 from a rhetorical perspective. It is argued that the dominant rhetorical strategy in this section can be described as the use of the authority of Scripture in order to present an allegorical exposition of the Hagar-Sarah events. This allegorical exposition is dominated by a metaphorical contrast between two types of sonship, namely sonship characterised by slavery and sonship characterised by spiritual freedom. This is done in order to urge the Galatians to remain “free”, that is not to yield to Paul’s opponents. Furthermore the metaphorical contrast is used to vilify the opponents as their point of view is categorised as “slavery”. Lastly a number of supporting rhetorical techniques are pointed out.